RESPON PERTUMBUHAN DAN HASIL KACANG HIJAU (Vigna radiata L.) VARIETAS VIMA 3 DAN LOKAL PARANGTRITIS PADA CAMPURAN PUPUK ANORGANIK - Sidang Aji Sampurna; Maryani, Yekti; Pamungkas, Djoko Heru (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to determine the interaction between various inorganic fertilizer treatments and varieties on the growth and yield of green beans. The research was conducted in September - December 2022 in Bungkus Hamlet, Parangtritis Village, Kretek District, Bantul Regency, Special Province of Yogyakarta. The study was arranged in Complete Randomized Block Design (RAKL) which consisted of 2 factors, namely types of inorganic fertilizers with 4 levels (N, P and K) and varieties with 2 levels (Vima 3 and Local Parangtritis). Analysis of the results using Duncan's Multiple Range Test (DMRT) at 5% level. The results showed that there was no interaction between the types of inorganic fertilizers and varieties on the growth and yield of green bean plants. Treatment of various inorganic fertilizers did not show a significant difference to the growth of green beans, except for the variable number of leaves, number of pods per plant, and yield per hectare. Treatment of mixed inorganic fertilizers N, P, K gave the highest green bean yields. The treatment of mungbean varieties showed significantly different results on the growth of mungbeans, except for the variable plant height, number of pods and seed weight. The green bean variety Vima 3 gave higher yields than the local variety Parangtritis. Keyword: Inorganic fertilizers, growth and yield, green beans, varieties